Sub23 e +65: Cohousing em Abraveses, Viseu - Gonçalo José Ferreira dos Santos Pinto (2022)
This dissertation, entitled "Sub23 e +65 - Cohousing em Abraveses, Viseu", comes from a will to present a project's design, that serves as a starting point for reflection about some problems that burden modern society. The project of both a nursing home and youth residence rises as study subject, that owes its interest to its potential dimension and plurality of spaces as well as its technical and safety requirements. It aligns with the concept of cohousing, that seems to be a potential solution for the challenges that are inherent to this housing model. It's a place where a strong connection between public and private spaces is mandatory - living quarters, social spaces, commercial and health care areas share the same building. There spaces are connected and simultaneously, demand individuality, with different levels of intimacy. The main focus of this paper is the well-being of the future residents of the proposed establishment. It has the purpose of being an harmonious, relaxing and calm building, while being, at the same time, an active and stimulating place. Above all, it aims to be a place that can be called a home. However, it will be a collective building whose users will vary on a regular basis. Having these themes as a starting point, this work aims to give answers to the matters of spatiality, and to better understand the daily life of the users. The main goal is to focus on the themes that look not just into the individual interest of the user, but also into the collective interests of the community. The architectonic thinking will be influenced by all this questions.